PERILAKU DAN MAKNA VERBA DALAM BAHASA MADURA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study is aiming at studying the categoryand the meaningof verb in Madura language.The problem to study is how to know: form or morphological category, syntactic category.and meaning of verbsin Madura languagein enjo'-iyo. Research method applied in this study is descriptive-qualitative method. The data of this study is synchronic which is gained by having interview through open questionnaire. Thoughstem and base are singular,stem can only stand alone when it is imperative. Transitive can be mono-transitive, transitive, and transitive intransitive. Passiveconstruction can be categorizedas anti-active, and imperative can be categorizedas anti-passive. Basedon the meaningof verbin Madura languageconsists of causativeverb, reciprocalverb, reflexiveverb, locativeverb, repetitive verb, and imperative verb.